2020
DOI: 10.1186/s12917-020-02326-2
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and antimicrobial resistance profiles of bacterial species in stray cats, hospital-admitted cats, and veterinary staff in South Korea

Abstract: Background: Antimicrobial resistance is becoming increasingly important in both human and veterinary medicine. According to the One Health concept, an important step is to monitor the resistance patterns of pathogenic bacteria. In this study, the antimicrobial susceptibility patterns and trends of bacteria isolated from stray cats, hospital-admitted cats, and veterinary staff in South Korea between 2017 and 2018 were investigated. Results: The minimum inhibitory concentrations of different antibiotics for Stap… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 34 publications
4
11
0
Order By: Relevance
“…The antimicrobial options for empirical therapy can be compromised in companion animals ( Prescott et al, 2002 ; Jung et al, 2020 ) basically due to: (1) the increased incidence in the last years of antimicrobial-resistant bacteria such as MDR Enterococcus spp., Enterobacter spp., P. aeruginosa and K. pneumoniae , and (2) the extended AMR to other antimicrobial families (i.e., aminoglycosides, fluoroquinolones, and carbapenems). Of note, the results obtained from pets of this study are similar to those reported in human hospitals in Spain ( ESTUDIO EPINE-EPPS, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The antimicrobial options for empirical therapy can be compromised in companion animals ( Prescott et al, 2002 ; Jung et al, 2020 ) basically due to: (1) the increased incidence in the last years of antimicrobial-resistant bacteria such as MDR Enterococcus spp., Enterobacter spp., P. aeruginosa and K. pneumoniae , and (2) the extended AMR to other antimicrobial families (i.e., aminoglycosides, fluoroquinolones, and carbapenems). Of note, the results obtained from pets of this study are similar to those reported in human hospitals in Spain ( ESTUDIO EPINE-EPPS, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the presence of Proteus isolates from dogs with imipenem CMI90 > 4 mg/L is highly suspicious for carbapenemasa production. To prevent the selection of BLEEs and carbapenem- resistance profiles in both human and animal medicine, is very important to implement the One Health approach, and monitor the resistance patterns of these pathogenic bacteria in companion animals ( ESTUDIO EPINE-EPPS, 2017 ; Nigg et al, 2019 ; Jung et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sampling, isolation, identification, antimicrobial susceptibility tests, and phenotypic characterization of Enterobacterales were previously studied [ 24 , 25 ]. In total, 91 Enterobacterales isolates carrying ESC resistance genes (51 E. coli , 17 K. pneumoniae , five K. oxytoca , four S. marcescens , seven S. liquefaciens , and seven E. cloacae ) were collected from companion animals (56 hospital-admitted dogs, 23 stray dogs, 11 hospital-admitted cats, and one stray cat, Table 5 ).…”
Section: Methodsmentioning
confidence: 99%
“…PCR amplification of entire bla CTX-M , bla TEM , and bla SHV genes was performed as previously described [ 24 , 25 ]. For bla CTX-M -positive isolates, PCR and DNA sequencing were carried out for CTX-M-subtype detection.…”
Section: Methodsmentioning
confidence: 99%
“…For carbapenemase gene, the most prevalent carbapenemase gene were bla KPC and bla NDM , accounted for 51.6% and 35.7%, respectively in all carbapenemresistant Enterobacteriaceae (CRE) strains isolated from 2016 to 2018 across China (Han et al, 2020). Since 2000, CTX-M blactamases have been identified as the most widespread ESBL (Jung et al, 2020). The mecA and mecC were both included in UTI-HMGS for the surveillance of MRSA, which is a leading cause of deadly hospital-acquired infections (Lamontagne Boulet et al, 2018).…”
Section: Discussionmentioning
confidence: 99%